2021
DOI: 10.6000/1927-5129.2014.10.06
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Relationship Between Serum Cholesterol and Triglyceride to Glaucoma: A Case Control Study

Abstract: Purpose/Aim: primary Open-angle glaucoma (POAG) is an asymptomatic, progressive optic neuropathy characterized by enlarging optic disc cupping and visual field loss. POAG is a major cause of blindness and is characterized by progressive degeneration of the optic nerve and is usually associated with elevated intraocular pressure. Regarding the fact that dyslipidemia has a relationship with some ophthalmic diseases such as cataract, it sounds that the same relationship also exists with POAG. Therefore, it was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…Our results show that high serum lipid levels are associated with an increased risk of POAG. These findings are comparable to those of Davari et al ,[ 19 ] who studied 40 patients with POAG and 40 healthy individuals and found that the mean levels of cholesterol (211.18 ± 51.91 mg/dl in cases, 162.38 ± 39.56 mg/dl in controls) and triglyceride (165.92 ± 88.58 mg/dl in cases, 99.46 ± 43.08 mg/dl in controls) were significantly higher in cases than in controls, as was the proportion of patients with hypercholesterolemia and hypertriglyceridemia. They also noted a positive association between POAG and dyslipidemia (OR = 7.14 for hypercholesterolemia, OR = 16.9 for hypertriglyceridemia).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that high serum lipid levels are associated with an increased risk of POAG. These findings are comparable to those of Davari et al ,[ 19 ] who studied 40 patients with POAG and 40 healthy individuals and found that the mean levels of cholesterol (211.18 ± 51.91 mg/dl in cases, 162.38 ± 39.56 mg/dl in controls) and triglyceride (165.92 ± 88.58 mg/dl in cases, 99.46 ± 43.08 mg/dl in controls) were significantly higher in cases than in controls, as was the proportion of patients with hypercholesterolemia and hypertriglyceridemia. They also noted a positive association between POAG and dyslipidemia (OR = 7.14 for hypercholesterolemia, OR = 16.9 for hypertriglyceridemia).…”
Section: Discussionsupporting
confidence: 93%
“…They also noted a positive association between POAG and dyslipidemia (OR = 7.14 for hypercholesterolemia, OR = 16.9 for hypertriglyceridemia). [ 19 ] In our study, the mean total cholesterol levels (205.24 ± 36.90 mg/dl in cases, 177.68 ± 22.56 mg/dl in controls) and mean serum triglyceride levels (150.42 ± 49.55 mg/dl in cases, 130.84 ± 23.16 mg/dl in controls) were significantly higher in cases than in controls. Additionally, significantly higher levels of LDL were noted in cases than in controls (139.50 ± 31.03 mg/dl in cases, 114.96 ± 17.73 mg/dl in controls).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Consequently, while preserving its activity, cata-lase may in some way contribute to the compensation of oxidative stress in plasma. However, as we have reported previously, patients with POAG demonstrated intensive lipid peroxidation processes in spite of increased activity of catalase [27,28].…”
Section: Discussionsupporting
confidence: 69%
“…Because an increased production of superoxide anions in the vascular wall contributes to endothelial dysfunction in POAG, it is important to investigate the factors contributing to increased endothelial permeability in patients with POAG. The analysis of the literature on endothelial dysfunction demonstrated that the problem is still relevant and the mechanism of the development of endothelial dysfunction in POAG is still poorly understood [20,[26][27][28][29].…”
mentioning
confidence: 99%